Long-term exercise training and inflammatory biomarkers in healthy subjects: a meta-analysis of randomized controlled trials - Wang, Ya-Hai; Tan, Jingwang; Zhou, Huan-Huan; Cao, Meng; Zou, Yu (Frontiers in Psychology, 2023)
Objective: This meta-analysis investigated the effect of long-term exercise training (ET) including aerobic, resistance, and multicomponent ET on the levels of inflammatory biomarkers in randomized controlled trials (RCTs) involving healthy subjects. Methods: We searched seven databases for articles until May 1st, 2023. A random-effect meta-analysis, subgroup analysis, meta-regressions as well as trim and fill method were conducted using STATA 16.0. Result: Thirty-eight studies were included in the meta-analysis, involving 2557 healthy subjects (mean age varies from 21 to 86 years). Long-term ET induced significantly decreased in the levels of interleukin-6 (IL-6) (SMD -0.16, 95% CI -0.30 to -0.03, p=0.017), C-reactive protein (CRP) (SMD -0.18, 95% CI -0.31 to -0.06, p=0.005), as well as tumor necrosis factor alpha (TNFα) (SMD -0.43, 95% CI -0.62 to -0.24, p<0.001). Subgroup analysis revealed that Long-term ET conducted for more than 12 weeks and exercise of moderate intensity had greater anti-inflammatory effects. Meta-regression analysis showed that the reduction in CRP level induced by long-term ET was weakened by increasing exercise intensity. Conclusion: Long-term ET induced significant anti-inflammatory effects in healthy subjects. Long-term ET-induced anti-inflammatory effects were associated with exercise of moderate intensity and training conducted for more than 12 weeks.